Preliminary fuselage structural configuration of a flying-wing type airline - Cheng, Yun (Cranfield University, 2012)
The flying-wing is a type of configuration which is a tailless airplane accommodating all of its parts within the outline of a single airfoil. Theoretically, it has the most aerodynamic efficiency. The fuel consumption can be more efficient than the existed conventional airliner. It seems that this configuration can achieve the above mentioned requirements. According to these outstanding advantages, many aircraft companies did a great deal of projects on the flying-wing concept. However, the application was only for sport and military use; for airliner, none of them entered production. FW-11 is a flying-wing configuration airliner which is a design cooperation between Cranfield University and Aviation Industry Corporation of China (AVIC). Aiming the spatial economic and environmental needs, this 200-seat airliner would attract attention from airline companies for cost saving and environmental protection. Before start, this program is designated for a new generation commercial aircraft to compete with the existing same capability airliner, such as Airbus A320 and Boeing 767. As the first team of this program, the aim is to finish the conceptual design and prepare the relevant document for next two teams that will perform preliminary and detail design. As a member of FW-11 program and as part of the GDP, the author has been through the four conceptual design stages: engine manufacturers, aircraft family issues, structure design and the establishment of 3-D CAD model. The aim of IRP study is to focus on the initial fuselage design.
Keywords: Preliminary design; Flying-wing; multi-bubble; structure initial design; AVIC program